Torrefaction of oil palm fronds (OPF) as a potential feedstock for energy production processes - Thuraiya, Thaim; Ruwaida, Abdul Rasid; Wan Muhamad Syafiq, Wan Ismail (VGTU Press, 2019)
Oil palm fronds (OPF) and trunks contribute the highest biomass availability compared with other oil palm wastes. At the moment, they are usually left on the ground around the plantation area to decompose naturally and fertilize the soil. Previous researchers have focused on torrefaction of wood residues and other agricultural biomass with less atten¬tion has been paid to the utilization of Malaysia’s biomass such as OPF. Therefore, in this study, torrefaction of OPF was conducted in a tubular reactor at temperatures between 200 and 300 °C and residence time of 30 min. The results reveal an improved heating value as the temperature was increased, from 16.81 to 20.32 MJ/kg after the torrefaction process. The van Krevelen diagram also proved that torrefaction OPF could be classified as an intermediate, between raw OPF and coal. This proves the potential of OPF as one of the alternative feedstocks for energy production process through torrefaction.